Game of Demiurges in Maldeojo, by Huilo Ruales Hualca - Jiménez Coello, Hans (2026)
Considering that the grotesque studies on the work of Ruales Hualca have overlooked the figure of the demiurge, this analysis focuses on its characterization in the character of Fetiche and on the presence of a second demiurge through Fantoche. The concept of the demiurge allows for a critique of how the archetypes and expectations that regulate bodies and ways of being have both individual and collective impacts. Furthermore, this study delves into the use of demiurgy employed by Huilo Ruales, enriching the scholarship that regards the Ibarra-born writer as an heir to Valle-Inclán’s aesthetic. The methodology is based on an analysis of the novel Maldeojo (2018), drawing on the bibliography on esperpento, literary criticism, and selected reflections by Roland Barthes.